Avaliação do óleo essencial de Lippia origanoides na dieta, manejo e transporte de pacus Piaractus mesopotamicus - Rômullo Guilherme dos Santos Almeida (2024)
The constant search for phytotherapeutic additives that function as immunostimulants, improving the resistance of fish to health and management challenges and resulting in greater zootechnical performance of the animals, can function as an alternative to the use of chemotherapeutic and antimicrobial products. Chemotherapy drugs can increase production costs, with possible contamination of meat and water that is released into the environment and lead to the emergence of pathogens resistant to these drugs. Therefore, this study aimed to evaluate the effects on zootechnical performance, anesthetics and as a sedative of Lippia origanoides essential oil for the pacu Piaractus mesopotamicus, a species of commercial importance for Brazilian aquaculture, by evaluating growth, accumulated survival rate, hematological, immunological, biochemical, residual deposition and histological changes of the gills. Chapter 2 evaluated the zootechnical performance and cumulative survival rate after thermal challenge of juvenile pacu P. mesopotamicus. No differences (p>0.05) were observed for zootechnical performance between treatments. After the challenge, no significant differences (p>0.05) were observed in the cumulative survival rate, only in the absolute values for 1.5 and 2.0 mL kg-1 of Lippia origanoides essential oil (OELO). The OELO between 1.0 and 2.0 ml kg-1 does not affect zootechnical performance, however 2.0 mL kg-1 of OELO demonstrated potential to reduce the absolute mortality rate. In chapter 3, the hematological effects and modulation of the ventilatory frequency of the OELO as an anesthetic for pacus were determined. The anesthetic induction and recovery times and the ventilatory frequency (VF) of the fish (n = 48; 29.94 ± 6.69 g) were determined at different concentrations of OELO (0, 25, 50, 100, 200 and 400 µL L-1). According to the results of the first experimental trial, a new trial was carried out (n = 36; 29.25 ± 5.90 g), evaluating the effects of 0, 50 and 200 µL L-1 at different times (1 hour and 24 hours post-induction). Most blood variables returned to levels considered normal for the species 24 hours after anesthesia. Therefore, an OELO concentration of 200 µL L-1 can be considered safe for use before biometric handling of P. mesopotamicus. In chapter 4, the effects of OELO (0, 5, 10, 15 and 20 μL-1) in the transport water (4 hours) of pacu P. mesopotamicus were evaluated on hematological, immunological, biochemical, residual depletion and histological evaluation of the gills variables. No differences (p>0.05) were observed for hematological parameters between treated fish in relation to non-transported fish, erythrocytes were different (p